Heterogeneity of speech disorders in Parkinson’s disease: potential for classification, diagnostics and therapy - E. E. Vasenina; O. S. Levin (Медицинский совет, 2020)
Introduction. Speech disorders in Parkinson’s disease are a very common clinical sign. The structure of speech disorders is at the moment not fully understood, there is no unified approach to classification, therapy effects have not been studied.Materials and methods: 324 PD patients were primarily included in the study, and from those the patients showing clinically significant speech disorders (22,4%) were selected. All the patients were assessed for motor disorders (UPDRS part 3), cognitive disorders (Addenbrooke’s cognitive examination), as well as affective disorders.Results: by means of cluster analysis we identified 4 subtypes of speech disorders as dysphasia (adynamic, disprosodic, constructive, and logopenic). None of the forms was associated with parkinsonism severity and general severity of cognitive impairment, which allowed to consider dysphasia as a separate clinical syndrome. Disprosodic dysphasia differentiated by severity of axial symptoms (F value = 3.279, p < 0,05), adynamic dysphasia was associated with more pronounced apathy (F value = 4,2, p < 0,01), constructive dysphasia – with impairment of visual-spatial functioning (F value 29,93, p<0,0001), while logopenic dysphasia was associated with more severe attention deficiency.Conclusion: Speech disorders in PD are heterogeneous and can be regarded as manifestations of dysphasia. Identification of various subtypes will allow for optimizing the treatment of PD patients.